La ciencia política en Colombia. Reflexiones sobre su quehacer investigativo. (2020)
The article focuses on analyzing the state of scientific research in political science in Colombia. Therefore, the investigation delves into the examination of the groups that are recognized and endorsed by Colciencias. In this way, useful information is provided on the areas of study in which the research groups in the country are focused, their geographical location, the public or private character and the gender of the members assigned to them. Among the main findings, we discovered a discipline focused mainly on conflict, security and peace research, together with international relations. At the same time, there is a lack of attention in the topics of comparative politics, methodology and political economy. Finally, the study raises the need to promote greater leadership of women in front of the groups and consolidate research in political science outside the main cities of Colombia